2022
DOI: 10.7759/cureus.33179
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Digital Cutaneous Melanocytic Tumor With CRTC1::TRIM11 Fusion

Abstract: A cutaneous melanocytic tumor with CRTC1::TRIM11 fusion (CMTCT) was recently described as a novel superficial tumor with melanocytic differentiation and harboring a unique in-frame translocation, CRTC1::TRIM11. This emerging entity can occur at any age and is known to be a low-grade malignant neoplasm with limited follow-up data. There are no available guidelines for the management and treatment of this tumor. This neoplasm has been found in the extremities, head and neck, and trunk. Here, we present the first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…All but one case displayed indolent behavior. Since then, 34 new cases have been published 3–5 . Although 21 of these patients have remained disease free with no evidence of recurrence after a median follow‐up of 37 months (range: 12–168 months), three cases displayed aggressive behavior.…”
Section: Figurementioning
confidence: 99%
See 3 more Smart Citations
“…All but one case displayed indolent behavior. Since then, 34 new cases have been published 3–5 . Although 21 of these patients have remained disease free with no evidence of recurrence after a median follow‐up of 37 months (range: 12–168 months), three cases displayed aggressive behavior.…”
Section: Figurementioning
confidence: 99%
“…Another case had multiple positive regional lymph node metastases. Notably, neither of these tumors displayed any defining features that would otherwise predict an aggressive course 3,4 . However, a 30‐year‐old man with CTCT on the hip harboring TERT promoter variant developed regional inguinal lymph node and pulmonary metastases at 18 and 36 months, respectively 5 …”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…High expression of TRIM11 was observed in advanced stage gliomas, while low expression was associated with poor differentiation and favorable prognosis 21 . Additionally, TRIM11 can activate MAPK or PI3K/AKT signaling pathways to promote tumor cell proliferation, invasion, and migration 22 . Shang et al identified that TRIM11 suppresses ferritinophagy in pancreatic ductal adenocarcinoma 23 .…”
Section: Introductionmentioning
confidence: 99%